Cellulase immobilized by sodium alginate-polyethylene glycol-chitosan for hydrolysis enhancement of microcrystalline cellulose. (August 2021) - Wang, Yang; Feng, Chenyu; Guo, Rongxin; Ma, Yifang; Yuan, Yu; Liu, Yanping
Graphical abstract: Highlights: Cellulase was immobilized on sodium alginate-polyethylene glycol-chitosan. The relative enzyme activity remained 59.42 % after 5 cycles. The optimal conditions for hydrolysis was identified by Box-Behnken design. The cumulative reducing sugar yield was increased by 22.68 %. The proportion of amorphous area of microcrystalline cellulose was decreased. Abstract: A novel method of immobilizing cellulase on sodium alginate(SA)-polyethylene glycol(PEG)-Chitosan(CS) enables make the cellulase to be used repeatedly. The matrix of the immobilized cellulase was detected and characterized using Fourier transform infrared spectroscopy and scanning electron microscope. In addition, microcrystalline cellulose was hydrolyzed by the immobilized cellulase and its microstructure was further analyzed for comparison. The results showed that PEG added into SA-immobilized cellulase increased the porosity of matrix, then the hydrogen bond was formed between PEG and SA; and adding CS could form the polyelectrolyte membrane, it would reduce the disintegration of the carrier to improve the stability of the carrier. Meanwhile, the activities of immobilized cellulase and free enzyme were compared. In addition, the conditions for the SA-PEG-CS-immobilized cellulase to hydrolyze microcrystalline cellulose (MCC) were optimized by response surface method (RSM), and the interaction between independent variables was explored by analysis of variance (ANOVA). The overall yield of reducing sugar of the MCC hydrolyzed by SA-PEG-CS-immobilized cellulase was 22.68 % higher than that of the free cellulase after reusing it for 5 cycles. The strength of O3 -H-O5 was enhanced and the proportion of amorphous area was decreased.